The growing role of designated communicators in the monitoring of patients with left ventricular assist device in the era of the COVID pandemic. (14th October 2021) - Sobieszczanska-Malek, M; Szymanski, J; Zaleska-Kociecka, M; Burczynska, B; Kusmierczyk, M; Zielinski, T
Abstract: Background: Left ventricular assist devices (LVAD) are increasingly implanted in patients with end-stage heart failure. Patients require special care in terms of the safety and effectiveness of therapy, but during pandemic lockdown it is much more difficult to achieve. For many years at our institution, apart from routine personal visits, we have been using the REMEDIZER® internet communicator for remote care in LVAD group of patients. Objective: - evaluation of the safety and effectiveness of remote monitoring in the care of patients with LVAD during the COVID pandemic – evaluation of the safety of remote monitoring with a designated communicator instead of personal visits Methods: During the lockdown period (01/03/2020 - 31/12/2020), 72 patients (3 female) pts mean age 54.7±12, 1 years with LVAD were monitored. For epidemiological reasons, the number of personal visits has been reduced in favor of telephone consultations and an increased volume of data entered into the REMEDIZER® internet communicator. The data collected in this period were compared with the data collected on 1 March 2019 - 31 December 2019, when: 53 pts (1 female) mean age 56, 2±11, 78 years were routinely, personally controlled at the Center for at least every 3 months and had blood, echo and LVAD examinations. Patients entered pump parameters: flow, motor speed, power consumption, pulse and blood pressure, body weight and temperature, at least twice a day (morning and evening) INR and dose of warfarin used were also reported. The number of complications during LVAD support was assessed: death or heart transplantation major complications: stroke, hemorrhage, pump thrombosis also other like arrhythmias requiring ICD intervention, hospitalization. Results: Mean time of monitoring from hospital discharge after LVAD implantation to the end of observation in 2020 cohort was 651±486 days compared to 586±508, days in 2019 cohort In 2019, personal visits were performed significantly more often, 94 v. 17 (p<0.05), while remote visits (by phone or internet) were significantly more frequent in 2020 (2033 v. 1390). In 2019 patients were hospitalized significantly more often (28 vs. 10), but if we considered urgent hospitalizations, the differences were not statistically significant (9 vs. 8). In 2020, 5 patients (6, 94%) died compared with 4 (7, 55%) in 2019 (NS). In 2020, 9 patients (12, 5%) were transplanted v. 3 (5, 66%) in 2019. We observed 22 episodes of major complications in the 2020 cohort vs 20 in 2019 (NS); 11 ICD interventions vs 13 in 2019 (NS). Conclusions: Replacing routine personal visits with increased patient self-control and constant remote contact with the center allowed a safe organization of patient care during COVID-19 pandemic The use of REMEDIZER® internet communicator dedicated for LVAD patients for remote care control proved to be effective and safe to control LVAD patients. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The study is funded by the National Center for Research and Development, Poland